2014
DOI: 10.1103/physrevb.89.045403
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-bath-driven decoherence of mixed spin systems

Abstract: The decoherence of mixed electron-nuclear spin qubits is a topic of great current importance, but understanding is still lacking: while important decoherence mechanisms for spin qubits arise from quantum spin bath environments with slow decay of correlations, the only analytical framework for explaining observed sharp variations of decoherence times with magnetic field is based on the suppression of classical noise. Here we obtain a general expression for decoherence times of the central spin system which expo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
92
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(94 citation statements)
references
References 45 publications
1
92
0
1
Order By: Relevance
“…At CTs, the effect of the 29 Si on the electron spin coherence is strongly suppressed (though not completely removed), leading to coherence times of up to 100 ms. Previous studies have focused on quantum approaches to model electron spin decoherence from 29 Si nuclear spin baths [24,25]; however, performing such calculations near the CTs can be challenging due to the strongly correlated nuclear spin baths [24].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At CTs, the effect of the 29 Si on the electron spin coherence is strongly suppressed (though not completely removed), leading to coherence times of up to 100 ms. Previous studies have focused on quantum approaches to model electron spin decoherence from 29 Si nuclear spin baths [24,25]; however, performing such calculations near the CTs can be challenging due to the strongly correlated nuclear spin baths [24].…”
mentioning
confidence: 99%
“…For the Si:Bi system interacting with a 29 Si nuclear spin bath (I i = 1/2 and natural abundance 4.7% throughout the host lattice), the system Hamiltonian is divided into three parts [24,25]:…”
mentioning
confidence: 99%
“…The quantum dynamics of a single qubit or central spin coupled to a spin environment [1] has been widely studied theoretically in several different areas, including quantum information sciences [2][3][4][5][6][7][8][9], quantum decoherence [10][11][12][13][14][15][16][17][18][19], and excitation energy transfer [20][21][22]. One of the most promising candidates for quantum computation, solidstate spin systems, are inevitably coupled to their surrounding environment, usually through interactions with neighboring nuclear spins [6,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…A particularly striking example has been identified recently in spin systems with special coherence sweet-spots termed 'optimal working points' (OWPs), [10][11][12][13][14] where theory and experiment found that coherence times can change by orders of magnitude with even small variations in applied magnetic field (∼ 200 G). A drastic change in back-action occurs via changes to the states of the central spin only: the change in external field has little direct effect on the bath spin-pair dynamics.…”
mentioning
confidence: 99%
“…45 It is thus also of practical importance to understand whether dynamical decoupling and OWP techniques may be advantageously combined for a quantum bath of nuclear spins. For donor electronic qubits in silicon, it is known that due to inhomogeneous broadening from naturally-occurring 29 Si spin isotopes, there is a significant gap between the T 2 ∼ 100 ms in natural silicon near an OWP, 12,13 and the T 2 ∼ 2 s in isotopically enriched 28 Si with a low donor concentration at the same OWP. 13 Also, dynamical decoupling may be useful when it is convenient to operate with the magnetic field close to but not exactly at the OWP.…”
mentioning
confidence: 99%